1978
DOI: 10.1093/nar/5.10.3881
|View full text |Cite
|
Sign up to set email alerts
|

Nucleosome conformation: pH and organic solvent effects

Abstract: Monomer nucleosomes (v ) from chicken erythrocyte nuclei were examined in aqueous buffers (8>pH>3) and in solvent mixtures (i.e., water and ethanol, ethylene glycol, dioxane, dimethyl sulfoxide, 2-methyl-2,4-pentanediol, polyethylene glycol, sucrose, or urea). Circular INTRODUCTIONOur present understanding of nucleosome structure is based primarily upon studies conducted in vitro, Recent biochemical studies suggest, however, that nucleosome conformation is altered in chromatin that is active in transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
1

Year Published

1979
1979
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 24 publications
(20 reference statements)
1
15
1
Order By: Relevance
“…We have formerly utilized such nuclei and found that this depletion does not destroy the typical nuclear chromatin structure on the nucleosomal level (13). Our findings do not comply with results yielded by investigating isolated nucleosomes at low pH under equilibrium conditions (27). It seems, therefore, justified to assume that the chromatin gained by lysing such nuclei offers the potential for complementing a number of studies in which a distinction between the effect of high ionic strength and the properties of the H 1-deficient chromatin eo ipso would appear desirable.…”
Section: Discussioncontrasting
confidence: 92%
“…We have formerly utilized such nuclei and found that this depletion does not destroy the typical nuclear chromatin structure on the nucleosomal level (13). Our findings do not comply with results yielded by investigating isolated nucleosomes at low pH under equilibrium conditions (27). It seems, therefore, justified to assume that the chromatin gained by lysing such nuclei offers the potential for complementing a number of studies in which a distinction between the effect of high ionic strength and the properties of the H 1-deficient chromatin eo ipso would appear desirable.…”
Section: Discussioncontrasting
confidence: 92%
“…As discussed earlier, the sulfhydryl group of histone H3 becomes reactive over the same range of urea concentrations (121,123). A potentially important generalization has been made from the denatura tion of core particles by urea and by othel' denaturants, namely that the DNA conformation changes coincidently with a change in the alpha-helix content of the core histones (174).…”
Section: Relation Of Histones To the Dnamentioning
confidence: 99%
“…The nucleosome core is a fragile object (van Holde, 1988). Systematic study of the stability of nucleosome cores isolated from the nuclei of somatic cells has determined the temperature, pH, and salt concentrations at which histone-DNA interactions are disrupted (Zama et al, 1978;Gordon et al, 1979;Libertini and Small, 1980;Burch and Martinson, 1980;Burton et al, 1978;Walker and Wolffe, 1984). An important aspect of nucleosome core stability is the sensitivity of histone-DNA interactions to dilution.…”
mentioning
confidence: 99%